A Perspective Study on Network Intrusion Detection System Using Various Approaches - Soundarraj, K; Ravichandran, M (International Journal of Computer Sciences and Engineering, 2019)
With the increasing demand on automation and computers, one of the chief issues in the present decade has been to build a secure network, to prevent against malicious activities on the network. The process which monitors and analyzes the communication of network and detects intrusion and anomalies is termed as Intrusion Detection System (IDS). By handling such huge voluminous network traffic-based IDS also creates new issues. To overcome this, many statistics, machine learning and artificial intelligence-based approaches were started evolving. This paper focuses on the importance of such techniques in the field of intrusion detection by performing detailed survey. It presents a general overview of IDS, types of IDs and various methods used for classification. It also describes the several methods and the importance of IDSs in information security.